O desempenho econômico da mesorregião Norte Central paranaense: um enfoque sob a economia espacial - Rodrigues, Daiane Alves (2014)
This research analyzed the regional economic performance profile in the central north of Paraná, from 1999 to 2010, under the spatial economy focus. The group of micro regions belonging to this zone has similar features; however it has different dynamics in its productive activities. Despite of this specific zone economic growth, the industry and service sector had great performance in the period, however the agriculture revealed a small growth. The great majority of the micro regions showed a similar profile, taking advantage from the sectors with bigger growth to boost their activities. An analytical research was used as methodology, fundamentally from secondary data collected from IBGE and IPARDES. As first step it was researched the VAB from the primary, secondary and tertiary sectors to verify the micro regions performance from 1999 to 2010 calculating the geometric growth rate and it was detected that great section of the micro regions grew specially in industry and services sections, however some of them such as: Astorga, Apucarana, Faxinal and Ivaiporã could get greatest positive results in the period and in all sectors. In the second step it was necessary to understand the structural-differential behavior of the micro regions by the method shift-share, which reflected bigger dynamism again in the industry and services sections. Based specially in the differential behavior, the same micro regions were in more relevant position, they had in the location factor a competitive advantage, which contributed to spotlight those micro regions, as it is explained by the spatial economy. The micro regions with higher economic growth have as similarity the proximity to big agglomerations (in this case Londrina and Maringá) that radiate attractions effects to these localities, enhanced by the Poles Theory (Perroux) and the Central Places theory (Christaller and Losch) as well as Alfred Marshall helps to explain the fact that the industries are located near the production factors, reducing transport expenses, developing an urbanization economy and providing after that the trading and the services growth.